OPTIMALISASI PERAN PENDAMPING PROSES PRODUK HALAL DALAM MENINGKATKAN KESIAPAN SERTIFIKASI HALAL DAN DAYA SAING PRODUK UMKM - Lubna Laelatul Farhan Lubna; Eli Dahlia (Jurnal Abdi Inovatif : Pengabdian kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute one of the key sectors contributing to regional economic growth. However, many MSME owners have not yet obtained halal certification due to their limited understanding of the applicable regulations, certification procedures, and inadequate digital literacy in utilizing online certification systems. This issue is also evident among MSMEs in Majalengka Regency, particularly those operating in the food and beverage sector. This community service program aimed to enhance the knowledge and readiness of business actors in fulfilling halal certification requirements through the optimization of the role of halal product process assistants. The program was implemented through several activities, including socialization of halal certification regulations and requirements, digital literacy training on the use of the Halal Information System (SiHalal) application, and direct assistance in preparing and completing the necessary documents for halal certification. The program was conducted over a period of three months and involved 50 MSME participants. The results indicated an improvement in participants' understanding of halal regulations and halal certification procedures, as reflected in the increase in average pretest and posttest scores. In addition, participants demonstrated improved ability to prepare business administrative documents systematically and successfully registered accounts on the SiHalal application as an initial step in the halal certification process. Nevertheless, several challenges related to the use of digital technology were identified, particularly among participants aged over 40 years, highlighting the need for more intensive assistance. Overall, the mentoring activities proved effective in enhancing the readiness of MSME actors to undertake the halal certification process while simultaneously strengthening their capacity to utilize digital technology in supporting more competitive and sustainable business development.